2008
DOI: 10.1007/s11106-008-9039-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic assessment of the Cu-Ti-Zr system. II. Cu-Zr and Ti-Zr systems

Abstract: The thermodynamic assessment of the Cu-Zr and Ti-Zr systems is carried out using the CALPHAD method. The Gibbs energy of Cu-Zr liquid alloys is described by the ideal associated solution model. The excess Gibbs energy of Ti-Zr liquid alloys and Cu-Zr and Ti-Zr solid solutions is descried by models with Redlich-Kister polynomials. The Gibbs energy of Cu-Zr intermetallic compounds is described by models taking into account their formation enthalpy and entropy. A set of self-consistent parameters of the models is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Comparing the results of our previous calculations for a number of glass-forming binary systems (Ni−(Ti, Zr, Hf) [28]; (Co, Ni, Cu)−(Ti, Zr, Hf) [29,30]; Cu−Ti [10]; Cu−Zr [21]; Cu−Hf [33]) with known concentration range of amorphization has shown that it is advisable to be guided by the relative position of metastable liquidus lines of terminal solid solutions and position of corresponding It was shown in [21] and [33] for the Cu−Zr and Cu−Hf systems, respectively, that the concentration range for the formation of bulk amorphous alloys could be correctly predicted as a concentration interval between the metastable liquidus lines at glass transition temperature.…”
Section: Modeling Of Metastable Transformations With Participation Ofmentioning
confidence: 83%
See 2 more Smart Citations
“…Comparing the results of our previous calculations for a number of glass-forming binary systems (Ni−(Ti, Zr, Hf) [28]; (Co, Ni, Cu)−(Ti, Zr, Hf) [29,30]; Cu−Ti [10]; Cu−Zr [21]; Cu−Hf [33]) with known concentration range of amorphization has shown that it is advisable to be guided by the relative position of metastable liquidus lines of terminal solid solutions and position of corresponding It was shown in [21] and [33] for the Cu−Zr and Cu−Hf systems, respectively, that the concentration range for the formation of bulk amorphous alloys could be correctly predicted as a concentration interval between the metastable liquidus lines at glass transition temperature.…”
Section: Modeling Of Metastable Transformations With Participation Ofmentioning
confidence: 83%
“…The parameters of models describing the thermodynamic properties of phases in the boundary binary systems are taken in accordance with our previous thermodynamic assessments: Cu−Ti [20], Cu−Zr, and Ti−Zr [21]. To describe the ternary Cu−Ti−Zr system, it was needed to model the properties of ternary nonstoichiometric phases: solid solutions based on pure components, liquid phase, binary intermetallic compounds for which homogeneity regions were found in the ternary system, and ternary intermetallide τ 1 .…”
Section: Thermodynamic Models and Assessment Of The Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic parameters for the Ti-Zr and Ti-Mo binary systems are taken from the assessment of Turchanin et al [15] and Shim et al, [16] respectively. The mobility parameters for the self-diffusion coefficients of bcc Ti and bcc Zr are taken from our earlier papers on the mobilities of Ti-V [9] and Nb-Zr [17] binary systems, respectively.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The calculated Ti-Zr phase diagram according to the thermodynamic assessment of Turchanin et al [15] is given in Fig. 1.…”
Section: The Ti-zr Systemmentioning
confidence: 99%